1998
DOI: 10.1007/s004410051151
|View full text |Cite
|
Sign up to set email alerts
|

The CNS lesion scar: new vistas on an old regeneration barrier

Abstract: Scar formation represents a reaction of nervous tissue to any form of physical injury. Research over the past decade has demonstrated that the scar composed of glial cells and several extracellular matrix molecules constitutes an obstacle to axon regeneration in the CNS. This review briefly summarizes the current knowledge on (a) the structural and functional features of the lesion scar and (b) the development of therapeutic interventions to override this regeneration barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
146
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(157 citation statements)
references
References 63 publications
(75 reference statements)
5
146
0
2
Order By: Relevance
“…These obstacles are: (i) scar tissue formation after tissue injury (1-7); (ii) gaps in nervous tissue formed during phagocytosis of dying cells after injury (3,(8)(9)(10)(11)(12)(13)(14); (iii) factors that inhibit axon growth in the mature mammalian CNS (1,3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20); and (iv) failure of many adult neurons to initiate axonal extension (3, 8-12, 15, 17, 21, 22). In this paper, we describe the creation of a permissive environment for axonal regrowth using a synthetic biological nanomaterial that self assembles in vivo, with components that break down into beneficial building blocks and produce no adverse effects on the CNS.…”
mentioning
confidence: 99%
“…These obstacles are: (i) scar tissue formation after tissue injury (1-7); (ii) gaps in nervous tissue formed during phagocytosis of dying cells after injury (3,(8)(9)(10)(11)(12)(13)(14); (iii) factors that inhibit axon growth in the mature mammalian CNS (1,3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20); and (iv) failure of many adult neurons to initiate axonal extension (3, 8-12, 15, 17, 21, 22). In this paper, we describe the creation of a permissive environment for axonal regrowth using a synthetic biological nanomaterial that self assembles in vivo, with components that break down into beneficial building blocks and produce no adverse effects on the CNS.…”
mentioning
confidence: 99%
“…Typically in mammals, there is a subsequent proliferation and hypertrophy of astrocytes around the injury site. 8,9,48,71 . Specifically, reactive astrogliosis is denoted by increased immunoreactivity of glial fibrillary acid protein (GFAP), which is a distinct cellular marker of astrocytes.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Specifically, reactive astrogliosis is denoted by increased immunoreactivity of glial fibrillary acid protein (GFAP), which is a distinct cellular marker of astrocytes. 14,48,[71][72][73][74]111 It has been demonstrated that reactive adult astrocytes upregulate the production of laminin and neurotrophin C. 75,76 In addition to the endogenously present myelinassociated neurite growth inhibitory constitutents, reactive astrocytes form an astroglial scar that acts as a physical and/or chemical barrier to axonal regeneration. 8,35,72,77,78 Proximity to the lesion epicentre determines whether the reactive glial environment will be growth supportive or inhibitory.…”
Section: Experimental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,10 Although di erent glial cells participate in the scar formation, the reactive astrocytes play a predominant role re¯ected by the very high levels of glial acid ®brillary protein (GFAP). 11 A landmark of secondary tissue loss following CNS trauma is a devastating decrease of intracellular energy substrates. 12 This energy loss is due to vascular damage and the subsequent reperfusion induced endothelium damage.…”
Section: Introductionmentioning
confidence: 99%